2017
DOI: 10.1159/000479688
|View full text |Cite
|
Sign up to set email alerts
|

One-Year Follow-Up of Girls with Precocious Puberty and Their Mothers: Do Psychological Assessments Change over Time or with Treatment?

Abstract: Background: To determine whether psychological characteristics of girls with variations of early puberty and their mothers change over time and with treatment in girls with central precocious puberty (CPP). Methods: Girls with CPP, premature adrenarche (PA), and early normal puberty (ENP) completed psychological assessments at baseline and after 1 year along with their mothers. All girls with CPP were treated with GnRH analogs. Psychological effects of group and time were examined using 2 × 3 mixed ANOVAs. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 38 publications
1
23
0
1
Order By: Relevance
“…Early evidence has indicated that precocious puberty may lead to certain psychological or social problems, which are considered to bother parents and may affect the clinical treatment of CPP 40 . However, according to the results of the included studies, GnRHa treatment did not worsen the cognitive, psychological and social problems of children with ICPP and has the potential to reduce problems in some children, which was consistent with recent evidence 41,42 …”
Section: Discussionsupporting
confidence: 86%
“…Early evidence has indicated that precocious puberty may lead to certain psychological or social problems, which are considered to bother parents and may affect the clinical treatment of CPP 40 . However, according to the results of the included studies, GnRHa treatment did not worsen the cognitive, psychological and social problems of children with ICPP and has the potential to reduce problems in some children, which was consistent with recent evidence 41,42 …”
Section: Discussionsupporting
confidence: 86%
“…Baseline psychological assessments of cognitive competence, peer acceptance, physical competence, and maternal acceptance were, on average, normal in all groups. After 1 year of follow-up, findings were “largely reassuring regarding concerns of adverse psychological consequences of early puberty in girls” [25]. A study of 15 girls with CPP and 15 age-matched controls reported the only detectable difference in a large battery of tests was that treated girls showed higher emotional reactivity on 1 of 2 tests.…”
Section: Do Girls With Cpp Have More Psychological Problems Than Prepmentioning
confidence: 99%
“…Because of conflicting conclusions in the medical literature in this area, no clear consensus regarding the risk of psychopathology in children with CPP exists [37]. Although some studies have indicated increased stress and anxiety in girls with CPP [38, 39], others have found no differences in psychological functioning as compared with control subjects [40, 41]. This is an area in which more research is definitely needed.…”
Section: Criteria For Treatmentmentioning
confidence: 99%